Algae of biological soil crusts from sand dunes of the Danube Delta biosphere reserve (Odesa Region, Ukraine) - Mikhailyuk, T.I.; Vinogradova, O.M.; Glaser, K.; Rybalka, N.; Demchenko, E.M.; Karsten, U. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2021)
The species composition of algae from biological soil crusts (biocrusts) on the surface of sand dunes (Black Sea coast, Primorske, Izmail District, Odesa Region, Ukraine) was investigated. Samples were collected from three coastal localities: Katranivska Spit, Zhebryianska Bay and Zhebryianska Ridge. The latter two localities are in the territory of the Danube Delta Biosphere Reserve. The samples were investigated by direct microscopy, followed by a culture approach. 60 species from Chlorophyta (32), Cyanobacteria (16), Streptophyta (7) and Ochrophyta (5) were identified. Representatives of the cyanobacterial genera Microcoleus Desmazières ex Gomont, Coleofasciculus M.Siegesmund, J.R.Johansen & T.Friedl, Nostoc Vaucher ex Bornet & Flahault, Hassallia Berkeley ex Bornet & Flahault, and streptophytes from the genus Klebsormidium P.C.Silva, Mattox & W.H.Blackwell dominated in the studied biocrusts. Phylogenetic analyses based on 16S/18S rRNA as well as 16S-23S ITS/ITS-1,2 regions were undertaken for some strains of cyanobacteria and eukaryotic algae. As a result, species identification and their position in respective phylogeny was refined, as well as aiding the discovery of some interesting and rare species. New genera and species were described (Streptosarcina arenaria Mikhailyuk & Lukešová and Tetradesmus arenicola Mikhailyuk & P.Tsarenko); with two genera (Nodosilinea R.B.Perkerson & D.A.Casamatta and Pleurastrosarcina H.J.Sluiman & P.C.J.Blommers) and four species reported for the first time for the flora of Ukraine (Nodosilinea epilithica Perkerson & Casamatta, Pseudomuriella aurantiaca (W.Vischer) N.Hanagata, Pleurochloris meiringensis Vischer, Pleurastrosarcina terriformae Darienko, W.J.Kang, Orzechowski & Pröschold). Comparison of the results from this study with similar investigations at Cape Kazantip (Sea of Azov, Ukraine) and at two islands of the Baltic Sea (Rügen, Usedom, Germany) revealed that sand composition and texture, as well as climate type of the respective region, are the main factors determining species composition of algae and cyanobacteria in biocrusts of maritime dunes.